Prevalence of Bovine Tuberculosis Gross Lesions in Doukkala slaughterhouses, Morocco - Hamid, Aboukhassib; Abdelali, Bitar; Mohammed, Haraji; Hind, Yahyaoui Azami; Mohammed, Bouslikhane (European Scientific Journal, ESJ, 2019)
In Morocco, tuberculosis (TB) is a major zoonotic disease with very serious hygienic and economic impacts. Our study aimed to investigate bovine tuberculosis in two Moroccan slaughterhouses in Doukkala area based on the observation of macroscopic gross lesions. 4198 cattle were examined for tuberculosis lesions during the period of end of May 2014 to July 2015.The results showed that 64.4% of cattle with TB lesions were male with a dominant age of less than or equal to 2 years (67.2%). Females represented only 35.6% with a dominant age between 4 and 8 years (62.3%). The dominant breed was the cross breed of imported and local breeds with 95.4%. Tuberculosis-like lesions were observed in 194 animals (4.6%) including 10 (5.15 %) of generalized and 184 (94.85 %) of localized lesions, mainly encountered in the lungs (44.83%), the head lymph nodes (42.32%) the liver and its associated lymph nodes (9.41%). An estimated overall daily prevalence of 4.6% and a daily average of 5.4% (95% CI: 4.7 - 6.1%) were noted. Compared data obtained from the slaughter database 1.97 % (95% CI: 1.8 – 2.4), this prevalence is more than twice of estimated average (RR=2.34). This assumes that routine inspection leaves more than 50% of animals with suspicious lesions. On the other hand, 390 gross lesions were collected for culturing. An isolation frequency of Mycobacterium of 85.6% was obtained and the LPJ and Herrold seem to be the best culture media.